2012
DOI: 10.1111/j.1460-9592.2012.03876.x
|View full text |Cite
|
Sign up to set email alerts
|

Capsicum plasters on acupoints decrease the incidence of emergence agitation in pediatric patients

Abstract: Summary Aim:  To detect the effect of capsicum plasters on bilateral HT 7 acupoints for decreasing Emergence agitation (EA) in pediatric patients undergoing tonsillectomy and/or adenoidectomy. Background:  Emergence agitation with its incidence of 10% to 80% may have deleterious effects in postoperative period. Children may harm themselves and/or care providers who require extra nursing care and additional sedatives and/or analgesics that may cause a delay in discharge from hospital. The studies dealt with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 23 publications
(42 reference statements)
0
35
0
Order By: Relevance
“…This is also true in clinical settings, as others reported the acupuncture-like effect of the topical application of capsaicin on acupoints [56,57]. Capsaicin can cause conduction analgesia (or desensitization) [58,59].…”
Section: Discussionmentioning
confidence: 94%
“…This is also true in clinical settings, as others reported the acupuncture-like effect of the topical application of capsaicin on acupoints [56,57]. Capsaicin can cause conduction analgesia (or desensitization) [58,59].…”
Section: Discussionmentioning
confidence: 94%
“…9,10 The stimulation methods used in the previous studies are difficult to apply in daily clinical practice because they require special techniques or medications. Our method, however, is easy to apply in daily practice because it only requires PNS devices that are regularly used in operating theatres.…”
Section: Discussionmentioning
confidence: 99%
“…As noted above, acupuncture treatment is not strictly limited to needle insertion, with many practitioners employing other techniques, including moxibustion [1], low level laser [6], capsaicin plaster [9], and even simple manual acupoint massage (acupressure) [33]. …”
Section: Discussionmentioning
confidence: 99%
“…Yet, rather than being stimulatory, Chow et al have found that laser actually inhibits peripheral nerves [8]. Similarly, the application of capsaicin to acupuncture points in bother upper [9] and lower [10] limbs results in identical effects to needle acupuncture, yet capsaicin induces neural conduction blockade rather than stimulation [11]. It is, of course, quite possible, that acupuncture employing needle insertion induces its clinical effect through an entirely different mechanism to that of laser acupuncture and capsaicin application to acupuncture points.…”
Section: Introductionmentioning
confidence: 99%